2009
DOI: 10.1063/1.3099605
|View full text |Cite
|
Sign up to set email alerts
|

Spectral statistics of the quenched normal modes of a network-forming molecular liquid

Abstract: We evaluate the density of states of the quenched normal modes of ST2 water, and their statistical fluctuations, for a range of densities spanning three regimes of behavior of a hydrogen bonded liquid: a lower-density regime of random tetrahedral network formation, in the vicinity of a liquid-liquid critical point, and in a higher-density regime of fragile glass-forming behavior. For all cases we find that the fluctuations around the mean spectral densities obey the predictions of the Gaussian orthogonal ensem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…We use the flexible version of the model and hence all degrees of freedom to calculate the Hessian (see Refs. [54,55,57] for a more detailed explanation of the formalism and method). (b) Spatial dependence of the amplitude of normal modes A max (r) in the Boson peak regime.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use the flexible version of the model and hence all degrees of freedom to calculate the Hessian (see Refs. [54,55,57] for a more detailed explanation of the formalism and method). (b) Spatial dependence of the amplitude of normal modes A max (r) in the Boson peak regime.…”
Section: Methodsmentioning
confidence: 99%
“…We use the flexible version of the model and hence all degrees of freedom to calculate the Hessian (see Refs. [54,55,57] for a more detailed explanation of the formalism and method).…”
Section: Methodsmentioning
confidence: 99%
“…This ensures all the eigenvalues are on same footing. The analytical fitting function used for unfolding need not be unique and, is generally different for different systems [30][31][32][33][34]. For this study, the eigenvalue spectra of all the correlation matrices generated is approximated extremely well by a function of the form…”
Section: Unfolding Of Datamentioning
confidence: 99%
“…In such a scenario, one settles for a model that captures the statistical properties of the energy spectrum. RMT finds extensive applications in the statistical studies of various complex systems such as quantum chaotic systems, complex nuclei, atoms, molecules, disordered mesoscopic systems [16][17][18][19][20][21][22][23][24], atmosphere [25], financial applications [26], complex networks [27], societal networks [28], network forming systems [29,30], amorphous clusters [31][32][33][34], biological networks [35], protein networks [36,37], and cancer networks [38] etc. In recent years, RMT has also been applied towards brain network studies in studying universal behavior of brain functional connectivity and has been effective in detecting the differences in resting state and visual stimulation state [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the spectra of these systems, which are in general system dependent, have established that the statistical properties of the spectral fluctuations can be associated with one of the three universality classes identified in RMT [48,49,55,56]. Vibrational spectra, obtained from computer simulations, of several disordered solids and liquid systems have revealed that the spectral fluctuations follow the Gaussian orthogonal ensemble (GOE) of RMT [46,[54][55][56][57]. Particularly, these studies have shown that the delocalized modes conform to GOE statistics while the localized modes were found to obey Poissonian statistics [51,57].…”
Section: B Level Spacing Statisticsmentioning
confidence: 99%